Enhancing the Robustness of a Three-Layer Security Electronic Voting System Using Kerberos Authentication - Nwogu, Emeka Reginald; Ahiara, Wilson Chukwuemeka; Aondohemba, Peter Mathew (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
The rapid advancements in technology have spurred interest in electronic voting systems as a means to modernize and enhance the democratic electoral process. However, ensuring the security and integrity of electronic voting systems remains a critical challenge. In this study, we present a highly secure and efficient model for an electronic voting system, featuring a robust three-layer security architecture that includes the device authentication, user authentication and network security. The proposed system incorporates Kerberos authentication and Advanced Encryption Standard (AES) to fortify device and user authentication. The segmentation of the system network into zones that includes the Virtual Private Network, the Public Network and the Demilitarized Zone also helps to mitigate potential cyber-attacks and fraudulent activities. Leveraging biometric security (fingerprint) and user tokens (voter's cards), the system ensures the accurate identification and authentication of voters, thereby enhancing the overall integrity of the voting process. Through a series of tests involving 500 enrolled users, the proposed electronic voting system demonstrated remarkable efficacy, achieving a 100 percent accuracy rate in ballot tallying. Having addressed key concerns related to security and transparency, the proposed voting system has the potential to instil trust and confidence in electoral processes.